Difuzija železovih ionov v kromitno magnezitnih gradivih - Mirtič, Breda (Kovine zlitine tehnologije, 1995)
Magnesia-chrome refractories decay because of differenc causes. Some damaging appearances have been already investigated. The present article describes the causes and kinds of iron diffusion into periclase and chromate aggregates which compose the magnesia-chrome refractory and formation of magnesium ferrite. Inversely, magnesium wustite is formed during iron diffusion out of periclase aggregates. Reactions depend on temperature, quantitz of iron and partial oxygen pressure in kiln. Magnesium ferrite and wustite formation influence the refractory brick porosity and consecutively its strength and mechanical resistance.
Keywords: gradiva; kromitno magnezitno gradivo; difuzija